1994
DOI: 10.1182/blood.v83.5.1348.bloodjournal8351348
|View full text |Cite
|
Sign up to set email alerts
|

DNA rearrangements proximal to the EVI1 locus associated with the 3q21q26 syndrome

Abstract: Specific rearrangements involving 3q21 and 3q26 are well documented in acute myeloid leukemia (AML). Aberrant expression of the Ecotropic virus integration-1 (EVI1) gene, located at 3q26, has been reported in individuals with AML and translocations or inversions of chromosome 3 long arm. We have studied six individuals with AML and inv(3)(q21q26) for disruptions to the EVI1 locus by in situ hybridization and long- range mapping. EVI1 transcripts have been detected in the blast cells of the two individuals avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…This may reflect breakpoint differences at the molecular level. The breakpoint in five cases with inv(3)(q21q26), including case 4 from this paper (case 1 in Levy et al, 1994) were shown to be localized 3' to the EVIl gene (Levy et al, 1994). Nucifora et al (1994) have shown that 3q26 contains three genes, EAP, MDSl and EVI1.…”
Section: Discussionmentioning
confidence: 52%
“…This may reflect breakpoint differences at the molecular level. The breakpoint in five cases with inv(3)(q21q26), including case 4 from this paper (case 1 in Levy et al, 1994) were shown to be localized 3' to the EVIl gene (Levy et al, 1994). Nucifora et al (1994) have shown that 3q26 contains three genes, EAP, MDSl and EVI1.…”
Section: Discussionmentioning
confidence: 52%
“…A brief characterization of the YACs is given in Table 1. YAC 14EE12 was isolated from the ICI library and contains the EVI1 gene as well as the FIM3 locus (Levy et al, 1994). It was kindly provided by V. J. Buckle (John Radcliffe Hospital, Oxford, UK).…”
Section: Fish With Yac Clonesmentioning
confidence: 99%
“…It has been shown that the incidence of 3q anomalies with breakpoints in q21 and q26 is higher than previously estimated and can be considered as frequent and specific chromosomal changes in myeloid malignancies . The breakpoints in both 3q regions are scattered over considerable distances (Morishita et al, 1992;Levy et al, 1994;Schnittger et al, in preparation).…”
Section: Introductionmentioning
confidence: 99%
“…Although the EVI1 gene is not expressed in normal haemopoietic cells, aberrant expression of the EVI1 gene has been reported in patients with 3q21q26 syndrome (Fichelson et al, 1992;Morishita et al, 1992). Recently, it has been shown that the EVI1 gene is transcriptionally activated in AMLs with t(3;3)(q21;q26) and inv(3)(q21q26) and that the chromosomal breakpoints at 3q26 in the translocation were 5 0 of the EVI1 gene, whereas the breakpoints in the inversion cases were 3 0 of the gene (Levy et al, 1994;Suzukawa et al, 1994). At 3q21, the breakpoints for both AMLs with t(3;3)(q21;q26) and inv(3)(q21q26) were found to cluster over a region of approximately 50 kb downstream of the Ribophorin I gene (Suzukawa et al, 1994).…”
mentioning
confidence: 99%